Pengaruh Beasiswa KIP Dalam Mendorong Keaktifan Mahasiswa Di Institut Agama Hindu Negeri Gde Pudja Mataram - Arika, I Gede; Darmayasa, I Made Indra; Kasih, I Gede; Pratama, I Wayan Pasek Indra; Dewi, Ni Putu Sasmika (Widya Sandhi, 2024)
Higher education in Indonesia faces challenges in achieving equitable access for all layers of society, particularly concerning economic factors. The Indonesia Smart Card Scholarship (KIP) program is expected to enhance student engagement as a solution. This research aims to explore the impact of the KIP Scholarship Program on student engagement at the Gde Pudja Mataram State Hindu Institute. This study employs a quantitative approach with a descriptive correlational research design involving 41 KIP scholarship recipients from the Hindu Economics Study Program. The results indicate that students' participation in academic and non-academic activities correlates positively with their overall engagement. These findings underscore the importance of scholarship programs and supportive activities in enhancing the quality of student experiences on campus and making significant contributions to the development of inclusive and effective higher education policies. In conclusion, the KIP Scholarship Program has a positive impact on student engagement, highlighting the importance of financial support and supportive activities in achieving equitable access to higher education.